2022
DOI: 10.1111/chso.12634
|View full text |Cite
|
Sign up to set email alerts
|

Healthy masculinity construction: The influence of race, faith and athletics

Abstract: Due to structural racism, young men living in urban cities-particularly Black and other youth of colour-are at risk for developing hegemonic, toxic masculine identities.However, through a positive youth development approach, sport can be used to promote healthy masculinity. This study explored the importance and meaning of masculinity, as well as influences of masculinity construction among 14 urban male youth who participated in a faith-based sport program. Findings from semi-structured interviews highlight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, this result of hearing a higher frequency of anti-LGBTQ + language in sport aligns with earlier research on the hyper-surveillance and policing of gender norms, specifically masculinity, in sport (Adams & Govender, 2008; Butler, 1990; Connell, 2008; Kimmel, 2008; Martino, 2000; McCreary, 1994; Metcalfe, 2018; Oransky & Fisher, 2009; Pascoe, 2005; Phoenix et al, 2003; Poteat, 2007; Poteat et al, 2007; Reigeluth & Addis, 2016, 2021; Renold, 2002). Further, this finding may speak to the necessity of promoting critical consciousness and other similar social justice life skills, namely healthy masculinity (Newman et al, 2023) and LGBTQ + allyship (Robinson et al, 2022), as they are both known to promote an inclusive and welcoming environment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, this result of hearing a higher frequency of anti-LGBTQ + language in sport aligns with earlier research on the hyper-surveillance and policing of gender norms, specifically masculinity, in sport (Adams & Govender, 2008; Butler, 1990; Connell, 2008; Kimmel, 2008; Martino, 2000; McCreary, 1994; Metcalfe, 2018; Oransky & Fisher, 2009; Pascoe, 2005; Phoenix et al, 2003; Poteat, 2007; Poteat et al, 2007; Reigeluth & Addis, 2016, 2021; Renold, 2002). Further, this finding may speak to the necessity of promoting critical consciousness and other similar social justice life skills, namely healthy masculinity (Newman et al, 2023) and LGBTQ + allyship (Robinson et al, 2022), as they are both known to promote an inclusive and welcoming environment.…”
Section: Discussionmentioning
confidence: 96%
“…As the self-esteem of cis white boys may be most impacted by anti-LGBTQ + language, the concept of POM as a factor in this relationship requires further investigation. In addition, toxic masculinity may be a related concept under the larger construct of hegemonic masculinity that may capture the way these norms are reinforced in educational sport settings (Newman et al, 2023). Future studies also can investigate if stigma competence may explain differential impacts of hearing anti-LGBTQ + language in sport among students of differing and intersectional identities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the participants in our study embraced a muscular body ideal, demonstrated strength, power, and confidence (i.e., disrupting certain gender stereotypes) (Podmore & Ogle, 2018), they also reproduced gendered norms by wearing minimal clothing both inside and outside of CrossFit. Although Cindy and the other women in the study claimed to be proud of and confident of their muscular bodies, confidence is typically construed as a masculine trait (Newman et al, 2023), and demonstrates a complex and paradoxical mix of masculinity/femininity and non-gendered subjectivity in CrossFit women’s body-sexuality expression (Howarth, 2013). Cindy’s confident display of her masculine/feminine body reportedly yielded comments from others about ‘showing off’, whereas Amanda worries about whether her partner will continue to find her sexually attractive and desirable with large ‘masculine’ trapezoid muscles.…”
Section: Discussion: Paradoxical Themes and Challenging Women’s Perfo...mentioning
confidence: 97%
“…This content helped ignite the role of a spiritual advisor to model emotional management (Givens et al 2016), which is certainly what Smith and Carlos needed in the aftermath of 1968. Budding research continues to highlight how Black male youth construct healthy masculinity within the context of a faith-based positive youth development sport program (Newman et al 2022). Community-based youth organizations should continue to provide agency to reimagine Black identities as progressive beyond pervasive biases and binaries, as Black students in high school develop strong proactive racial identities that symbiotically feed into academic success (Carter 2010).…”
Section: Discussionmentioning
confidence: 99%